2013
DOI: 10.1016/j.jjcc.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Plasma homocysteine is associated with ischemic findings without organic stenosis in patients with slow coronary flow

Abstract: The results of this study show that there is an important pathophysiologic link between the increased levels of plasma Hcy, the degree of ischemic findings, and the severity of slow flow in SCF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Although PLR was not as strong a predictor as NLR for lower HRR value, it was found to be significantly associated with NLR and HRR, suggesting the presence of a crucial link between inflammatory reactions and autonomic function in the CSX patients analyzed. Similarly, Timurkaynak et al [9] reported that the homocysteine level, known to be related with endothelial dysfunction and ischemic findings [31], was inversely correlated with DTS in patients with CSX, and our findings are in line with these reports. Our study extends these findings in two important ways.…”
Section: Discussionsupporting
confidence: 92%
“…Although PLR was not as strong a predictor as NLR for lower HRR value, it was found to be significantly associated with NLR and HRR, suggesting the presence of a crucial link between inflammatory reactions and autonomic function in the CSX patients analyzed. Similarly, Timurkaynak et al [9] reported that the homocysteine level, known to be related with endothelial dysfunction and ischemic findings [31], was inversely correlated with DTS in patients with CSX, and our findings are in line with these reports. Our study extends these findings in two important ways.…”
Section: Discussionsupporting
confidence: 92%
“…Angiographic findings demonstrated that HHCY was strongly correlated with slow coronary flow (SCF) phenomenon after PCI protacol [ 27 , 28 ], implying the possible correlation between HHCY and less IRA patency. Current evidence suggests that the microcirculation dysfunction and damage of endothelial cells caused by HCY-induced oxidative stress played an important role in SCF [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…hypertension, diabetes mellitus, dyslipidemia, hyperuricemia, smoking, chronic kidney disease), there were no significant factors associated with ischemia-like ECG. Further investigation involving a larger number of patients and more risk factors, such as high-sensitive C-reactive protein or homocysteine [36], may be needed.…”
Section: Discussionmentioning
confidence: 99%